1985
DOI: 10.1111/j.1365-2672.1985.tb01718.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of water on the resistance of spores to inactivation by gaseous ethylene oxide

Abstract: Standardized conditions for exposure to ethylene oxide were used to evaluate the resistance of spores dried for various times at different relative humidities and temperatures. Spores dried under conditions of high humidity exhibited low resistance to the sterilant, the resistance increasing as the relative humidity (RH) was decreased. Increasing the temperature of drying amplified this effect by reducing the time required for equilibration to a specific RH. Spores dried over a desiccant at 37 degrees C showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…On this model, the ratio of time constants should be Ϸ(577͞177) 2 ϭ 10.6, which is close to the observed ratio, 480 s͞48 s Ϸ 10. Y Various authors have studied the effect of RH on inactivation of bacterial spores by gas-phase ethylene oxide (25), formaldehyde (26,27), and chlorine dioxide [Chlorine Dioxide (ClO 2 ) Gas Phase Demonstration Project, U.S. Environmental Protection Agency Environmental Response Team Report, unpublished]. All of them reported that spore killing efficacy increased with RH, approaching 100% for RH greater than Ϸ70%, but opinions differed as to the role of humidity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On this model, the ratio of time constants should be Ϸ(577͞177) 2 ϭ 10.6, which is close to the observed ratio, 480 s͞48 s Ϸ 10. Y Various authors have studied the effect of RH on inactivation of bacterial spores by gas-phase ethylene oxide (25), formaldehyde (26,27), and chlorine dioxide [Chlorine Dioxide (ClO 2 ) Gas Phase Demonstration Project, U.S. Environmental Protection Agency Environmental Response Team Report, unpublished]. All of them reported that spore killing efficacy increased with RH, approaching 100% for RH greater than Ϸ70%, but opinions differed as to the role of humidity.…”
Section: Discussionmentioning
confidence: 99%
“…They found that small solutes such as water enter the cell rather easily, with q ϵ 1.0, whereas larger ones encounter more difficulty. Applying their experimental dependence of q on molecular volume to the gases that have been used to inactivate spores (25,(25)(26)(27), we estimate partition ratios q ϭ 0.94, 0.90, and 0.7 for formaldehyde, ethylene oxide, and chlorine dioxide, respectively. Admittedly, these values of q are not much smaller than unity, but they are based on observations in vegetative cells, not spores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation